NUMERICAL INVESTIGATION OF TURBULENT NATURAL CONVECTION IN AN INCLINED SQUARE ENCLOSURE (Journal of Engineering, 2009)
Two dimensional turbulent natural convection heat transfer and fluid flow inside an air filled inclined square enclosure differentially heated has been numerically studied. Fully elliptic Navier- Stockes and energy equations are solved using finite volume method. The problem is simulated for different angles of inclination ( 0   180deg. ) and Rayleigh numbers ( 8 16 10  Ra  10 ). The turbulence k-є model is used to model the effect of turbulence. The wall function approach is used to model the regions near the walls of the enclosure. The obtained results from this study show that the rate of heat transfer is increasedwith the increase of Rayleigh number and decreased with the increase of angle of inclination( 0   90deg. ).Also the induced vortices are strongly elongated with increase of Rayleigh number. The thickness of thermal boundary layer is decreased with the increase of Ra. The validation of the present code was done by comparing the computed results with the published ones. The comparison indicated a good agreement.